Altered ratio of proapoptotic and antiapoptotic proteins in different brain regions of female rats in model of post-traumatic stress disorder - CABADAK, HÜLYA; GÖREN, MEHMET ZAFER (WALTER DE GRUYTER GMBH, 2015)
Objective: The B-cell lymphoma/leukemia-2 (Bcl-2) family of proteins governs mitochondrial membrane permeability where the programmed apoptotic process is controlled by the balance between proapoptotic (Bax) and antiapoptotic (Bcl-2) proteins. We aimed to investigate the [Bcl-2]/[Bax] in different brain regions in a post-traumatic stress disorder rat model. Methods: Female Sprague-Dawley rats were exposed to dirty cat litter (trauma) for 10 min and the protocol was repeated 1 week later with a trauma reminder (clean litter) in reversed 12 h light/dark cycle. The rats received intraperitoneal saline, fluoxetine (2.5 mg/kg/day) or propranolol (10 mg/kg/day) for 7 days between exposure sessions. Following exposure to the trauma reminder, elevated plus maze experiments were done. Immunoblotting was used to quantify [Bcl-2] and [Bax] proteins in the homogenates of the dorsal hippocampus, the frontal cortex and the amygdaloid complex. Results: Fluoxetine reversed the increases in the anxiety indices and the freezing times. In the amygdaloid complex and the frontal cortex, the [Bcl-2]/[Bax] decreased in the traumatized control rats significantly (p<0.0001), but not in the dorsal hippocampus. Although the fluoxetine treatment reversed the apoptotic changes but propranolol failed and caused proapoptotic proteins to increase. Conclusion: These results may suggest a neuroprotective role for fluoxetine but not for propranolol.
Keywords: Dorsal hippocampus; amygdaloid complex; frontal cortex; Bcl-2; Bax; predator scent test; Western blot; cat litter; HIPPOCAMPAL VOLUME; BCL-2 FAMILY; CELL-PROLIFERATION; ANIMAL-MODEL; FLUOXETINE; PROPRANOLOL; APOPTOSIS; RESPONSES; PTSD; MRI